ANALISIS EFISIENSI PENGGUNAAN INPUT PRODUKSI USAHATANI SEMANGKA DI KECAMATAN NEGARA KABUPATEN JEMBRANA - Dewi, Ni Kadek Widya Sari; Saskara, Ida Ayu Nyoman (E-Jurnal Ekonomi dan Bisnis Universitas Udayana, 2023)
The agricultural sector is a very important sector, efficiency the use of land area, labor, and capital is an absolute thing for a farmer. The purpose of this study was to determine the effect of land area, labor, and capital to production as well as to find out efficiency and scale of production produced. Data used in research this is primary data, namely by distributing questionnaires to farmers watermelon in the State District of Jembrana Regency. Sample used in this study as many as 80 respondents. Using regression analysis techniques multiple linear. The results of this study indicate that the land area, labor, and capital have a simultaneous effect on production. Land area in partial positive and significant effect on production. Labor force partial positive and significant effect on production. Partial capital positive and significant effect on production. Efficiency level of area land and capital are already efficient and their use can still be increased and labor is not efficient so it does not need to be increased its use. Scale production is in a decreasing return of scale. Keywords: Total Production; Economic of Scale; Efficiency Input of Production.